EDUKASI PENGENALAN JURNALISTIK KEPADA GENERASI DIGITAL - Ahmad Junaidi; Riris Loisa; Sinta Paramita (Jurnal Bakti Masyarakat Indonesia, 2021)
The digital generation is a generation whose lives depend almost entirely on internet access. The ease of accessing information has both negative and positive sides. The negative side is that the digital era is a generation that is prone to cybercrime and is easily exposed to hoaxes through internet networks. There has been a lot of research in Communication Science that discusses the negative side of technological development. But on the other hand, the digital generation can create exciting content through social media. Kanaan Christian Senior High School initiated this potential to develop extracurricular activities that could improve students' abilities in journalism. The problem arises when there are no teaching resources that can educate students in the world of journalism. Therefore, the Faculty of Communication Sciences at Tarumanagara University seeks to inform people's lives through community service activities (PKM), to assist the Kanaan Christian High School in carrying out journalistic extracurricular activities by providing ongoing training. The movement was carried out on August 13, 2020, starting with an introduction to journalism, and the action was continued again on August 27, 2020, with the subject of getting to know the news. This activity increased students' understanding of the definition, the function of the press, the form of mass media, the purpose of the report, types of information, and the value of the news shown in statistical data. This activity is also a pilot project for the Faculty of Communication Sciences at Tarumanagara University in managing the target area.ABSTRAKGenerasi digital adalah generasi yang hampir keseluruhan kehidupannya bergantung kepada akses internet. Kemudahan mengakses informasi memiliki sisi negatif dan positif. Sisi negatif adalah generasi digital adalah generasi yang rawan akan kriminalitas siber dan mudah terpapar hoaks melalui jaringan internet, sudah banyak riset dalam Ilmu Komunikasi yang membahas sisi negatif dari berkembangnya teknologi. Namun disisi lain generasi digital mampu menciptakan konten-konten melalui media sosial yang menarik. Potensi Inilah yang digagas oleh SMA Kristen Kanaan untuk menciptakan ekstrakurikuler yang mampu meningkatkan kemampuan mahasiswa dalam dunia jurnalistik. Permasalahan muncul ketika tidak tersedia sumber daya pengajar yang dapat memberikan edukasi dunia jurnalistik kepada siswa-siswi. Oleh sebab itu Fakultas Ilmu Komunikasi Universitas Tarumanagara berupaya untuk mencerdaskan kehidupan masyarakat melalui kegiatan pengabdian kepada masyarakat (PKM), untuk membantu Sekolah SMA Kristen Kanaan dalam menjalankan ekstrakurikuler jurnalistik dengan memberikan pelatihan secara berkelanjutan. Kegiatan dilakukan pada tanggal 13 Agustus 2020 diawali dengan pengenalan tentang Jurnalistik dan kegiatan dilanjutkan lagi pada tanggal 27 Agustus 2020 dengan pokok bahasan mengenal berita. Hasil dari kegiatan ini adalah terdapat peningkatan pemahaman siswa-siswa terkait definisi, fungsi pres, bentuk media massa, definisi berita, jenis berita, dan nilai berita yang ditunjukkan dalam data statistik. Selain itu kegiatan ini menjadi pilot project bagi Fakultas Ilmu Komunikasi Universitas Tarumanagara dalam mengelola wilayah binaan.